Resetting the Stage Public Theatre Between the Market and Democracy - Klaic, Dragon (Intellect, 2012)
Commercial theatre is thriving across Europe and the UK, while public theatre has suffered under changing patterns of cultural consumption-as well as sharp reductions in government subsidies for the arts. At a time when the rationale behind these subsidies is being widely reexamined, it has never been more important for public theatre to demonstrate its continued merit. In Resetting the Stage, Dragan Klaic argues convincingly that, in an increasingly crowded market of cultural goods, public theatre is best served not by imitating its much larger commercial counterpart, but by asserting its artistic distinctiveness and the considerable benefit this confers on the public.